Analyzing Location-Based Accessibility to Dental Services: An Ohio Case Study - Mark W. Horner, PhD; Ana Karina Mascarenhas, BDS, MPH, DrPH (Blackwell Synergy, 2007)
Oral health is important to overall health. Therefore, dental services should be available and accessible in order for patients to receive care.